Uneven economic development - Ocampo, Jose Antonio (ed.); Vos, Rob (ed.) (London, 2008)
Inequality in the world is high and rising. The problem of global uneven development is central to, and inseparable from, the international development agenda. In Uneven Economic Development, leading economists and development experts examine the causes and implications of international economic divergences. This comprehensive and timely book reviews economic growth and structural change patterns since the 1960s, before critically reviewing the respective role and impact of trade liberalization, macroeconomic policies, governance and institutions on comparative national economic performance, particularly in developing countries. With country studies included to exemplify the issues at hand, this is a definitive guide to identifying, addressing and perhaps even finding a solution to this global phenomenon.
Keywords: Inequality